Galectin-3 and galectin-1 interactions in breast cancer therapy - Rani, Vanitha Innocent; Manohari, Aleti Lakshmi; Murali, Uthamalingam; Correya, Mary Anelia; Chakraborty, Tamalika; Bagchi, Preenon; Das, Gunamoni; Imran, Mohd (Universa Medicina, 2025)
Galectins, a family of β-galactoside-binding proteins, play critical roles in tumor progression, angiogenesis, and immune evasion, making them significant therapeutic targets in cancer treatment. By binding β-galactoside containing glycoconjugates, galectins modulate immune responses, apoptosis, and tumor development. The increasing recognition of their oncogenic roles has led to the development of carbohydrate- and peptide-based inhibitors that competitively bind to the carbohydrate recognition domain (CRD), disrupting galectin-mediated immune evasion, T-cell apoptosis, and angiogenesis. Given their intricate functions in the tumor microenvironment, a comprehensive evaluation of galectin inhibitors is warranted. This review synthesizes recent advancements in galectin-targeted therapies, including their mechanisms of action, efficacy in preclinical models, and potential synergy with chemotherapeutic agents and monoclonal antibodies. Despite promising developments, challenges remain in optimizing treatment regimens, overcoming resistance mechanisms, and identifying predictive biomarkers for patient stratification. Patient stratification, based on molecular or genetic profiles, is essential for enhancing therapeutic efficacy and ensuring personalized treatment approaches. A systematic literature search (2014–2024) was conducted using Google Scholar, ProQuest, Science Direct, and Scopus databases, with key terms including galectin inhibitors, cancer therapy, tumor microenvironment, immune evasion, and targeted therapy. This review highlights the role of galectin-1 and galectin-3 in breast cancer therapy, emphasizing their impact on tumor progression, immune modulation, and resistance to conventional treatments. Further translational research is necessary to refine clinical applications, optimize combination strategies, and establish biomarkers that enhance the integration of galectin inhibitors into existing treatment paradigms.